2006
DOI: 10.1016/j.visres.2005.10.019
|View full text |Cite
|
Sign up to set email alerts
|

In vitro dimensions and curvatures of human lenses

Abstract: The purpose of this study was to determine dimensions and curvatures of excised human lenses using the technique of shadowphotogrammetry. A modified optical comparator and digital camera were used to photograph magnified sagittal and coronal lens profiles. Equatorial diameter, anterior and posterior sagittal thickness, anterior and posterior curvatures, and shape factors were obtained from these images. The data were used to calculate lens volumes, which were compared with the lens weights. Measurements were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
97
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 31 publications
20
97
1
1
Order By: Relevance
“…The radius of curvature was 6.98mm for the anterior and 5.62mm for the posterior lens capsule. These were consistent with measurements of an accommodated lens (Rosen et al 2006;Hermans et al 2007Hermans et al , 2009Kasthurirangan et al 2011;Lanchares et al 2012). The geometry obtained using a pressure of 5-6mmHg had slightly greater thickness, but the dimensions were still within the range of measurements and human models (Augusteyn et al 2011).…”
Section: Resultssupporting
confidence: 83%
“…The radius of curvature was 6.98mm for the anterior and 5.62mm for the posterior lens capsule. These were consistent with measurements of an accommodated lens (Rosen et al 2006;Hermans et al 2007Hermans et al , 2009Kasthurirangan et al 2011;Lanchares et al 2012). The geometry obtained using a pressure of 5-6mmHg had slightly greater thickness, but the dimensions were still within the range of measurements and human models (Augusteyn et al 2011).…”
Section: Resultssupporting
confidence: 83%
“…Removal of the young lens from the eye will cause it to assume its most accommodated shape and decrease the equatorial diameter; thus, early in vitro studies that reported an increase in diameter with age were not necessarily showing an age-related increase. [48][49][50] An in vivo study of rhesus monkeys showed no change in LED with age, but the few in vivo human studies were equivocal. 15,41,47,51 The original MRI studies by Strenk and coworkers reported no change, while a more recent study comparing 18-to 29-year-old subjects to 60-to 70-year-old subjects found a slight increase of approximately 0.01 mm/ y.…”
Section: Discussion Accommodative Abilitymentioning
confidence: 99%
“…Most parameters needed for the sketches of the lenses were obtained or calculated from information available in the literature (4,5,12,25,28). Stepwise description of the construction from the available data is shown below.…”
Section: Calculation Of Volumes On the Theoretical Human Lensmentioning
confidence: 99%
“…Rosen et al (25), in their research on excised human lenses from cadavers (ages 20 to 99 yr), developed a linear regression analysis of curvatures of the anterior and posterior surfaces, as well as A-P sagittal thickness and equator diameter. Most of the formulas for creating the accommodated lenses were extracted from this study.…”
Section: Construction Of Human Lensesmentioning
confidence: 99%